Enhancing Rice Productivity through integration of Stress Tolerant Rice Varieties and Improved Nutrient Management Practices in Saline Areas of Bangladesh (Bangladesh Rice Journal, 2018)
The study was conducted in two locations of coastal districts Patuakhali and Satkhira during 2012 and 2013 T. Aman season. Stress tolerant rice varieties along with nitrogen application using prilled urea (PU), leaf color chart (LCC), urea super granule (USG), and rice crop manager (RCM) software based nitrogen (N) dose were examined. The objectives of the study were to identify the response of saline tolerant varieties to N fertilization on grain yield and profitability. Among the tested varieties, grain yield of BRRI dhan40, BRRI dhan41 and BRRI dhan54 were higher compared to BRRI dhan52 and BRRI dhan53 irrespective of location. There were no significant difference among the better performed varieties. Interaction effect of yield was significant in 2013 at Patuakhali but insignificant in both the locations in 2012. During 2013 in Patuakhali, the interaction effect of BRRI dhan40 × USG and BRRI dhan41 × USG produced higher grain yield and total N uptake. In Satkhira BRRI dhan54 and BRRI dhan40 performed better and produced higher grain yield and N uptake. Among the N application treatments USG application was the best compared to either LCC or RCM. The combination of BRRI dhan54×USG and BRRI dhan41×USG had more economic gains in both 2012 and 2013 in Patuakhali. The combination of BRRI dhan52×USG and BRRI dhan41×LCC appeared as themost profitable in Satkhira during 2013. Integration of saline tolerant varieties along with USG application could improve the yield of saline tolerant rice in saline environmentBangladesh Rice j. 2017, 21(1): 77-89